SURVIVORS OF SEX TRAFFICKING: HOW COULD THEY REVIVE? - Ike Herdiana; Suryanto Suryanto; Musta'in Mashud; Wiwin Hendriani (Journal of Educational, Health and Community Psychology, 2019)
The aim of this study is to identify factors which support survivors of sex trafficking to be resilient after their experience of trafficking. This is a qualitative study using case study approach. Data was collected through in-depth interviews with female sex trafficking survivors. The data analysis employed thematic analysis developed by Braun and Clark (2006). Result reveals some risk factors which survivors encountered, including personal factor, family poverty, family disintegration and disfunction, negative peer influence and juvenile delinquency, unsupportive community, and public stigma. Resilient survivors could basically overcome those risks and were supported by some personal protective factors, such as belief system, self-efficacy, effective coping skill, and personal motivation. Protective support could also be socially sourced, such as from family, peers, and shelter.Key words: resilience, risk factor, protective factor, social support, survivor, sex trafficking